HUBUNGAN MOTIVASI BELAJAR DENGAN MINAT WIRAUSAHA PADA SISWA JURUSAN TATA KECANTIKAN SMKN 7 PADANG - Melianti, Eka Oktaviani; Rahmiati, Rahmiati; Astuti, Murni (Journal of Home Economics and Tourism, 2016)
The background of this study because it shows the low student interest in entrepreneurship that were related to the lack of student motivation. This research is a quantitative descriptive correlational . The population in this study were students majoring Beauty SMKN 7 Padang year in 2014 and 2015 amounted to 86 people enrolled in Semester July-December 2015 ( Odd ) , the sampling technique is random sampling proportional number of 36 students. Mechanical analysis of the level of achievement of the respondents with a percentage formula , test requirements analysis using normality test and linearity test while analysis using the Pearson correlation coefficient Product Moment Correlation and continued with the t test for significance analysis of the correlation coefficient and hypothesis testing. The research showed the average score of respondents to the achievement of learning motivation variable indicates the percentage of 63% with a low category . Interest in entrepreneurship show a percentage score of 58% as well with a lower category . Relations between the two variables showed a correlation coefficient of 0626 with interpretation of strong relationships , t test showed a score of 4,129 > 2,021 so Ha is received . Â Keyword: Motivation interest, Â Entrepreneurship